Reliable Top-Left Light Convention Starts With Early Renaissance: An Extensive Approach Comprising 10k Artworks - Carbon, Claus-Christian; Pastukhov, Alexander (Frontiers in Psychology, 2018)
Art history claims that Western art shows light from the top left, which has been repeatedly shown with narrow image sets and simplistic research methods. Here we employed a set of 10,000 pictures for which participants estimated the direction of light plus their confidence of estimation. From 1420 A.D., the onset of Early Renaissance, until 1900 A.D., we revealed a clear preference for painting light from the top left—within the same period, we observed the highest confidence in such estimations of the light source.